Case control study of anxiety and depression among patients with miscarriage compared to those with successful pregnancy - Ng, Beng Kwang; Chuah, JN; Lim, Pei Shan; Shuhaila Ahmad,; Marhani Midin,; Nor Azlin Mohamed Ismail, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Miscarriage is one of the most common complications in pregnancy. There is emerging evidence that psychological impact following miscarriage is not unusual. Understanding the magnitude of psychological morbidity is important in the management of miscarriage. The main objective of this study was to compare the mean Hospital Anxiety and Depression Scale (HADS) score between women with miscarriage and women with successful pregnancy and to determine the socio-demographic factor and clinical characteristic that are associated with anxiety and depression. A descriptive case control study was conducted in a teaching hospital, over a period of 12-months (from October 2014 till September 2015). A total of 65 women were recruited with 32 women as the study group (miscarriage) and another 33 women as the control group (women with successful pregnancy). Mean HADS-anxiety score was higher in the study group compared to control group although it was not statistically significant (6.53 ± 3.427 vs 5.73 ± 2.875, p=0.309). Mean HADS-depression score was higher in the control group (4.34 ± 2.695 vs 4.45 ± 3.073, p=0.878). Women with maternal age more than 35 years and history of previous miscarriage had a higher tendency of anxiety and depression with higher mean HADS score. There was no association between other socio-demographic data and clinical characteristic with risk of anxiety and depression. As conclusion, there was no significant difference in women with miscarriage as compared to those with successful pregnancies, although older women with history of miscarriage had a preponderance to both disorders.